Contemporary perspectives on families, communities, and schools for young children - Saracho, Olivia N.; Spodek, Bernard (Contemporary perspectives in early childhood education., 2005)
Early childhood education has always been an enterprising one. Innovative models that provide connections among the family, community, and school of early childhood will continue to emerge through the years to acknowledge new educational ideologies, new social demands, and new knowledge. The issues addressed in this volume can provide new directions to prepare early childhood scholars, researchers, and practitioners to work as a team in these different settings.